1993
DOI: 10.1093/jnci/85.9.722
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alcohol Consumption on Plasma and Urinary Hormone Concentrations in Premenopausal Women

Abstract: This possible explanatory mechanism for a positive association between alcohol consumption and breast cancer risk merits further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
184
0
3

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 344 publications
(195 citation statements)
references
References 0 publications
8
184
0
3
Order By: Relevance
“…Experimental evidence among preand postmenopausal women provides additional support for the hypothesis. An intervention study among younger women found higher levels of oestrogens during consumption of two daily alcohol servings 4 . Alcohol exposure in postmenopausal women on oestrogen replacement therapy, a hormonal setting comparable to premenopausal status, led to a three-fold increase in serum E 2 24 .…”
Section: Discussionmentioning
confidence: 98%
“…Experimental evidence among preand postmenopausal women provides additional support for the hypothesis. An intervention study among younger women found higher levels of oestrogens during consumption of two daily alcohol servings 4 . Alcohol exposure in postmenopausal women on oestrogen replacement therapy, a hormonal setting comparable to premenopausal status, led to a three-fold increase in serum E 2 24 .…”
Section: Discussionmentioning
confidence: 98%
“…23 Although these mechanisms have not been precisely determined, the involvement of ER-mediated 14,15,58 estrogen-dependent [16][17][18][19] mechanisms, and hormone-independent mechanisms [20][21][22][23] has been suggested.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 Heavy drinking also has been linked to a high level of estrogen. 20,21 However, 53.9% of case mothers and 59.4% of control mothers reported alcohol consumption during the period 1 month before pregnancy to nursing, and 7.7% of case mothers and 9.0% of control mothers reported consumption of Ͼ 8 drinks per week. We observed no association of GCT with parental alcohol consumption, similar to an earlier study conducted by the Children's Cancer Group and the studies by Shu et al 8 and Johnson et al 10 In our study, only 4 case mothers and 1 control mother consumed Ͼ 14 cups per week during their first trimesters of pregnancy.…”
Section: Discussionmentioning
confidence: 99%